External quality assessment of AFB smear microscopy in public health centers - Leli Rachmawati; Riris Andono Ahmad (Berita Kedokteran Masyarakat (BKM), 2020)
Purpose: Microscopic examination is the main diagnostic method in countries with a high TB burden. Microscopic examination has an important role in TB case detection. The purpose of this study was to examine the quality of TB microscopic sputum examination at the level of the Public Health Center of Kulon Progo District, Indonesia.  Method: This research was a cross-sectional study with 21 Health Center subjects. A Structured questionnaire is used to record HR and logistical availability. Blinded rechecking was done for nine public health centers; data were analyzed to evaluate smear quality indicators and examine the error.  Results: The majority of laboratory workers were women (88.1%), aged 36-45 years (42.86%). Most laboratory staff had 11-20 years of work of length (42.86%). Logistical availability was good, but there were shortages of stock boxes, filter paper, and lens paper. A total of 762 slides from 9 health centers were rechecked. The positivity was 1.57%, error was 1.57% (FP= 41.7% FN= 58.3% sensitivity= 75% specificity= 98.9%). Major errors found 33.37% and 66.73% minor errors from 12 errors. Quality issues found were thickness (38%), salivary specimens (27%), and size (26%).  Conclusion: The performance of TB microscopic examination at The Health Center level in Kulon Progo was quite good, but it needs efforts to get better quality sputum to improve case detection